Response of Soil C and N, Dissolved Organic C and N, and Inorganic N to Short-Term Experimental Warming in an Alpine Meadow on the Tibetan Plateau - Cheng-Qun Yu; Zhen-Xi Shen; Xian-Zhou Zhang; Wei Sun; Gang Fu (The Scientific World Journal)
Although alpine meadows of Tibet are expected to be strongly affected by climatic warming, it remains unclear how soil organic C (SOC), total N (TN), ammonium N (NH4+-N) , nitrate N (NO3+-N), and dissolved organic C (DOC) and N (DON) respond to warming. This study aims to investigate the responses of these C and N pools to short-term experimental warming in an alpine meadow of Tibet. A warming experiment using open top chambers was conducted in an alpine meadow at three elevations (i.e., a low (4313 m), mid-(4513 m), and high (4693 m) elevation) in May 2010. Topsoil (0–20 cm depth) samples were collected in July–September 2011. Experimental warming increased soil temperature by ~1–1.4°C but decreased soil moisture by ~0.04 m3 m−3. Experimental warming had little effects on SOC, TN, DOC, and DON, which may be related to lower warming magnitude, the short period of warming treatment, and experimental warming-induced soil drying by decreasing soil microbial activity. Experimental warming decreased significantly inorganic N at the two lower elevations,but had negligible effect at the high elevation. Our findings suggested that the effects of short-term experimental warming on SOC, TN and dissolved organic matter were insignificant, only affecting inorganic forms.